2016
DOI: 10.4172/2375-4389.1000201
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of the Implementation of ERP according to Management Control System and the Global Performance of the Firm: Case of Tunisia

Abstract: Our present scientific perspective aims to be contingent. It will study the impact of the ERP on the main objective of management control system (MCS) which is the global performance improvement of the firm. This impact will depend on two main variables which are the strategy and the organizational structure. Dealing with the usefulness of ERP for successful companies, this paper firstly aims to identify the determinants of implementing an ERP "Enterprise Resource Planning systems" according to 29 management c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…Regarding social performance, this result is in line with Vadivel et al. (2021), Affes (2016) and Magnani et al. (2019) who confirmed that S-ERP systems and LM implementation had an important influence on each employee's role: employees displayed higher levels of competency and problem-solving capabilities, as well as increased cooperation, responsibility and continuous motivation to improve processes, allowing them to improve their productivity and reduce their resistance to change.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Regarding social performance, this result is in line with Vadivel et al. (2021), Affes (2016) and Magnani et al. (2019) who confirmed that S-ERP systems and LM implementation had an important influence on each employee's role: employees displayed higher levels of competency and problem-solving capabilities, as well as increased cooperation, responsibility and continuous motivation to improve processes, allowing them to improve their productivity and reduce their resistance to change.…”
Section: Resultssupporting
confidence: 78%
“…Regarding social performance, this result is in line with Vadivel et al (2021), Affes (2016) and Magnani et al (2019) who confirmed that S-ERP systems and LM implementation had an important influence on each employee's role: employees displayed higher levels of competency and problem-solving capabilities, as well as increased cooperation, responsibility and continuous motivation to improve processes, allowing them to improve their productivity and reduce their resistance to change. Moreover, this result is consistent with Bhattacharya et al (2019) who explained that lean management tools such as 5S can significantly reduce the injury rate and improve poor conditions of health and safety for employees, hence, improving their satisfaction, retention rate and securing high-quality prospective candidates because of good company reputation.…”
Section: Additional Analysissupporting
confidence: 78%
See 1 more Smart Citation
“…In order to record and monitor their endeavors, these corporations are collaborating with ERP providers to adapt their existing programs and develop modules dedicated to the tracking of pertinent data. In their research, Scholars in [39] conducted an investigation on a global food firm. The company implemented a carbon information management (CIM) module inside its ERP system.…”
Section: Fig 1 Evolution Of Erpsmentioning
confidence: 99%